2019
DOI: 10.1111/febs.15054
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of horizontal gene transfer on human health and physiology and how anthropogenic activity can affect it

Abstract: Horizontal gene transfer (HGT) is widespread among prokaryotes driving their evolution. In this paper, we review the potential impact in humans of the HGT between prokaryotes living in close association with humans in two scenarios: horizontal transfer in human microbiomes and transfer between microbes living in human managed environments. Although our vision is focused on the possible impact of these transfers in the propagation of antibiotic resistance genes or pathogenicity determinants, we also discuss pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…Hence, these opportunistic pathogens demand more attention than they have been given hitherto as the rich resistome repertoire (Supporting Information Table S4) identified in their genomes makes them reservoirs of ARGs (Yang et al ., 2017; Asante and Osei Sekyere, 2019; Decano et al ., 2019; Decano et al ., 2020). Moreover, being intestinal denizens and commensals, they can easily share these ARGs with facultative and obligate pathogens of humans and animals (Anderson and Seifert, 2011; Lerner et al ., 2017; Boto et al ., 2019; Osei Sekyere et al ., 2020b). Further, their presence on plants and the environment further suggests that they can share their ARGs with food‐borne and water‐borne pathogens (Anderson and Seifert, 2011; Lerner et al ., 2017; Boto et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these opportunistic pathogens demand more attention than they have been given hitherto as the rich resistome repertoire (Supporting Information Table S4) identified in their genomes makes them reservoirs of ARGs (Yang et al ., 2017; Asante and Osei Sekyere, 2019; Decano et al ., 2019; Decano et al ., 2020). Moreover, being intestinal denizens and commensals, they can easily share these ARGs with facultative and obligate pathogens of humans and animals (Anderson and Seifert, 2011; Lerner et al ., 2017; Boto et al ., 2019; Osei Sekyere et al ., 2020b). Further, their presence on plants and the environment further suggests that they can share their ARGs with food‐borne and water‐borne pathogens (Anderson and Seifert, 2011; Lerner et al ., 2017; Boto et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, being intestinal denizens and commensals, they can easily share these ARGs with facultative and obligate pathogens of humans and animals (Anderson and Seifert, 2011; Lerner et al ., 2017; Boto et al ., 2019; Osei Sekyere et al ., 2020b). Further, their presence on plants and the environment further suggests that they can share their ARGs with food‐borne and water‐borne pathogens (Anderson and Seifert, 2011; Lerner et al ., 2017; Boto et al ., 2019). Notably, the E. xiangfangensis strains found in rice from India had very few ARGs, albeit a few had multiple ARGs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids and the mobile genetic elements can be transferred through conjugative machinery. Bacteria in the gut environment have suitable conditions such as stable temperature, sufficient and permanent food resources, fixed physiological conditions, a large number of phages and bacterial cells, and plenty of opportunities for horizontal gene exchange [ 228 ]. It is revealed that the frequency of HGT in infants’ meconium and early fecal samples is higher than that in adults [ 229 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the human resistome in hospitalized and non-hospitalized populations is essential because the commensal microbiota can host ARGs and transfer it from and to pathogenic bacteria through horizontal gene transfer (HGT) [12], e.g., during an infection. In addition, HGT can also play a role in ARG mobilization to environmental communities by water and soil contamination [13] or the food we ingest [14,15]. The gut microbiome is of particular interest in the investigation of ARGs in the human microbiota since it is the largest, most diverse [16], highly exposed and affected by the intake of antibiotics.…”
Section: Introductionmentioning
confidence: 99%